Efficacy of Five Plant Extracts against Late Blight Disease of Tomato in Experimental Field - Islam, MM; Yesmin, D; Islam, S; Sultana, S; Azad, MAK (Journal of Environmental Science and Natural Resources, 2021)
This study was conducted to evaluate the efficacy of five plant extracts at different concentration for managing the late blight disease of tomato in experimental field of University of Rajshahi. The antimicrobial activity of five plant extracts such as Water gourd (Lagenaria siceraria), Eucalyptus (Eucalyptus chamadulonsis), Garlic (Allium sativum), Babla (Acacia nilotica) and Black Cumin (Nigella sativa) was tested for controlling the late blight disease causing pathogens Phytophthora infestans. The number of branching of tomato plant was highest in T15 treatment (Black Cumin 5%) and lowest in T5 (Garlic clove 10%) and T13 (Babla leaves 2.5%). The maximum number of late blight affected leaves were found inT1 (control) and T6 (Garlic clove (5%) treatments, and minimum in T14 (Black Cumin 10%). A highest number of fresh tomato was recorded in T14 (Black Cumin 10%) and T16 (Black Cumin 2.5%) whereas the lowest performance was observed in T7 (Garlic clove 2.5%). The highest number of late blight affected rotten tomato was observed inT12 (Babla leaves 5%) and the lowest in T5 (Garlic clove 10%). The yield of tomato (g) was found maximum in T15 treatment (Black Cumin 5%) and lowest in T6 (Garlic clove 5%) treatment. Environ. Sci. & Natural Resources, 12(1&2): 67-71, 2019